Pengaruh Model Pembelajaran Make A Match Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran IPA Kelas Iv Di UPTD SD Negeri 122390 Pematang Siantar - Junita Situmorang; Asister Fernando Siagian; Canni Loren Sianturi (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine the effect of the make a match learning model on students' learning motivation in grade IV science subjects at UPTD SD Negeri 122390 Pematang Siantar T.A. 2023/2024. In this research, researchers used quantitative research with experimental methods, with the aim of testing the hypotheses that have been established. The population and sample used in this research were all students in class IV-A UPTD SD Negeri 122390 Pematang Siantar, consisting of 21 students. The research data collection technique used by researchers is a questionnaire containing 25 questions. The data analysis used is a simple linear regression test analysis formula by paying attention to the coefficient of determination value. Based on this analysis, it was concluded that the make a match learning model affected students' learning motivation in grade IV science subjects at UPTD SD Negeri 122390 Pematang Siantar T.A. 2023/2024 there will be a positive influence, because the significant value for the influence of the make a match learning model variable (X) in a stimulant manner on the student learning motivation variable (Y) is 0,000<0,05 and the calculated t-value is 5.226 > t-table 2.093 with a calculated F value equal to 27,315, so it can be concluded that the hypothesis test Ha is accepted and Ho is rejected because it is based on the coefficient of determination (R Square) of 0.590 or the same as 59 %. which means that there is an influence of variable X on Y that is equal to 59%.